2000
DOI: 10.1091/mbc.11.8.2553
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cortical Flow Models In Vivo

Abstract: Cortical flow, the directed movement of cortical F-actin and cortical organelles, is a basic cellular motility process. Microtubules are thought to somehow direct cortical flow, but whether they do so by stimulating or inhibiting contraction of the cortical actin cytoskeleton is the subject of debate. Treatment of Xenopus oocytes with phorbol 12-myristate 13-acetate (PMA) triggers cortical flow toward the animal pole of the oocyte; this flow is suppressed by microtubules. To determine how this suppression occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 50 publications
3
33
0
1
Order By: Relevance
“…Furthermore, we observed a significant difference of myosin II activity between the leading tip and the soma in migrating neurons, indicating higher actomyosin contractility at the leading tip, as reflected also by the higher dynamics of the GC-like tip structure in migrating neurons. Since cortical actomyosin network is known to flow toward the region with higher cortical tension in animal cells (White and Borisy, 1983;Bray and White, 1988;Benink et al, 2000;Munro et al, 2004), we propose that the front-to-rear difference in actomyosin activity is responsible for driving the forward F-actin flow along the leading process, which in turn pulls the soma forward. We observed that soma translocation was accelerated and impeded when myosin II activity was elevated and inhibited at the front, respectively, whereas these manipulations at the rear end of the migrating neuron resulted in opposite effects.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, we observed a significant difference of myosin II activity between the leading tip and the soma in migrating neurons, indicating higher actomyosin contractility at the leading tip, as reflected also by the higher dynamics of the GC-like tip structure in migrating neurons. Since cortical actomyosin network is known to flow toward the region with higher cortical tension in animal cells (White and Borisy, 1983;Bray and White, 1988;Benink et al, 2000;Munro et al, 2004), we propose that the front-to-rear difference in actomyosin activity is responsible for driving the forward F-actin flow along the leading process, which in turn pulls the soma forward. We observed that soma translocation was accelerated and impeded when myosin II activity was elevated and inhibited at the front, respectively, whereas these manipulations at the rear end of the migrating neuron resulted in opposite effects.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, pharmacological disruption of microtubules increases F-actin-mediated contractility in many different cell types, including PC12 cells (Dennerll et al, 1988), fibroblasts (Danowski, 1989), retinal photoreceptor cells (Madreperla and Adler, 1989), and cardiac muscle cells (Tsutsui et al, 1993). In Xenopus oocytes, cortical F-actin flow could be suppressed by microtubule polymerization and enhanced by microtubule depolymerization (Canman and Bement, 1997;Benink et al, 2000). In addition, disrupting microtubules in chicken embryonic fibroblast resulted in increased phosphorylation of MLC (Kolodney and Elson, 1995), an effect that may help to fuel the F-actin flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les phénomènes contrôlant les réorganisations corticales et cytoplasmiques restent mystérieux. L'analyse des flux corticaux a toutefois été amorcée sur des oeufs de xénope artificiellement activés ainsi que sur leurs extraits cytoplasmiques [80]. Ces études mettent en évidence le rôle essentiel des microtubules dans le démarrage et l'orientation des flux corticaux dont la force motrice est le réseau d'acto-myosine cortical.…”
Section: Principes Cellulairesunclassified